Development of Kedah Natural Tourism Object in the Development of Leuser Ecowisata Area in Gayo Lues Regency - Amir Wahyu; Suwardi Lubis; Rujiman Rujiman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The aims of this study is to find out how the Development of Kedah Natural Tourism Object in the Development of Leuser Ecowisata Area. The descriptive method of this study  using qualitative research. The result shows that the SWOT analysis, Kedah Nature Tourism Objects shows that the position of the Kedah Nature Tourism Objects is in quadrant 1, this indicates that Kedah Nature Tourism Objects are in a very favorable position where the power possessed by Kedah Nature Tourism Objects such as the entrance to the Leuser Mountain which is one of the World Heritage has interesting flora and fauna and beautiful natural panorama and the air is still cool and clean can cover weaknesses and threats such as lack of facilities and infrastructure, unprofessional management and so forth. This position also makes Kedah Nature Tourism Objects can take all the opportunities available such as making Kedah Natural Tourism Objects a place for flora and fauna research for students and potential souvenirs, and so on.